DESIGN-PROJECTION OF MODERN DRESSES WITH FINISHING, CONSIDERING THE PROPERTIES OF FABRICS - Пашкевич, К. Л.; Єжова, О. В.; Кротова, Т. Ф.; Креденець, Н. Д.; Цзянсінь, Лю; Фесюк, І. Я. (Art and Design, 2020)
To study the specifics of design-projection of clothes with finishing, considering the properties of fabrics. The system approach, as well as the methods of system-structural and morphological analysis, are used. The current collections of women`s clothes, presented by modern designers, have been analyzed; the current fashion trends in manufacturing and finishing of dress fabrics and products, made from such fabrics, have been identified; the classification of types of finishing of clothes has been presented. The frequency of occurrence of different types of finishing in the collections of world-famous designers in 2011 – 2019 has been determined. Physical and mechanical properties of samples of dress fabrics have been studied, in particular: thickness, surface density, abruption characteristics; their interconnections have been identified. The recommendations on the selection of fabrics for the creation of modern women`s dresses using different types of finishing (flat, volumetric) have been developed. The interconnections between physical and mechanical parameters of dress fabrics are identified, and the recommendations on the selection of fabrics for the creation of modern women`s dresses using the finishing based on the tectonic approach are developed. The conducted set of scientific researches on the design-projection of women`s dresses, based on the tectonic approach, and the determination of physical and mechanical parameters of dress fabrics are the basis for the development of recommendations on the selection of fabrics for the manufacturing of dresses with a variety of finishes.